Exploratory Bifactor Analysis in Sport, Exercise, and Performance Psychology: A Substantive-Methodological Synergy - Myers, N.; Martin, J.; Ntoumanis, Nikos; Celimli, S.; Bartholomew, K. (American Psychological Association, 2014)
The first purpose of this study was to provide a brief and general case for the possible utility of the bifactor model in sport, exercise, and performance (SEP) psychology. The second purpose of this study was to demonstrate how exploratory and confirmatory forms of the bifactor model may be compared with each other and with more commonly used factor models in SEP psychology within a substantive-methodological synergy format. The substantive focus was the consideration of the bifactor model for the Psychological Need Thwarting Scale. The methodological focus was the bifactor model, which has a general factor, group factors, and a pattern matrix with a bifactor structure. The synergy was a demonstration of how exploratory and confirmatory bifactor analysis may be compared with each other and with more commonly used and more restrictive analyses (e.g., correlated first-order factor analysis, a second-order factor analysis), by reanalyzing existing data. A four-factor exploratory bifactor analysis on Psychological Need Thwarting Scale data produced an approximate bifactor structure that may offer a viable conceptualization for future research in this area. More broadly, when the underlying measurement theory is consistent with (a) a conceptually broad general factor, as well as (b) conceptually narrower group factors, there may be utility in comparing bifactor analysis to more commonly used and more restrictive factor analyses in SEP psychology.